Feeding Iran : Shi`i families and the making of the Islamic Republic - Wellman, Rose (University of California Press, 2021)
"Since Iran's 1979 Revolution, the imperative to create and protect the inner purity of family and nation in the face of outside spiritual corruption has been a driving force in national politics. Rose Wellman, through extensive fieldwork, examines how Basiji families, as members of Iran's voluntary paramilitary organization, are encountering, enacting, and challenging this imperative. Her ethnography reveals how families and state elites are employing blood, food, and prayer in commemorations for martyrs in Islamic national rituals to create citizens who embody familial piety, purity, and closeness to God. Feeding Iran provides a rare and humanistic account of religion and family life in the post-revolutionary Islamic Republic that examines how home life and everyday piety are linked to state power"--